Will Direct Oral Anticoagulants Have a Chance in Prosthetic Valves? - Mahmoud Abdelnabi (Radcliffe Medical Media, 2020)
Although there are abundant data highlighting the safety and efficacy of direct oral anticoagulants, to date, recent guidelines have limited their use to stroke prevention in patients with non-valvular AF, as well as in the prevention and treatment of venous thromboembolism and pulmonary embolism. Encouraging data about the off-label use of direct oral anticoagulants have been shown in several other indications, such as intracardiac thrombi, left ventricular thrombi and left atrial appendage, but a large sector of patients are still not addressed, such as valvular and prosthetic patients.